Corticotropin-Releasing Factor Receptor 1 in the Anterior Cingulate Cortex Mediates Maternal Absence-Induced Attenuation of Transport Response in Mouse Pups - Yoshida, Sachine; Ohnishi, Ryuko; Tsuneoka, Yousuke; Yamamoto-Mimura, Yuka; Muramatsu, Reiko; Kato, Tadafumi; Funato, Hiromasa; Kuroda, Kumi O. (Frontiers in Cellular Neuroscience, 2018)
A human infant initially shows non-selective sociality, and gradually develops selective attachment toward its caregiver, manifested as "separation anxiety". It was unclear whether such sophistication of attachment system occurs in non-human mammals. To seek a mouse model of separation anxiety, we utilized a primitive attachment behavior, the Transport Response, in that both human and mouse newborns immediately stop crying and stay immobile to cooperate with maternal carrying. We examined the mouse Transport Response in three social contexts: 30-min isolation in a novel environment, 30-min maternal absence experienced with littermates in the home cage, and the control home-cage condition with the mother and littermates. The pups after postnatal day (PND) 13 attenuated their Transport Response not only in complete isolation but also by maternal absence, and activated several brain areas including the periventricular nucleus of the hypothalamus, suggesting that 30-min maternal absence was perceived as a social stress by mouse pups after PND13. This attenuation of Transport Response by maternal absence was independent with plasma corticosterone, but was diminished by prior administration of a corticotropin-releasing factor receptor 1 (CRFR1) antagonist. Among 18 brain areas examined, only neurons in the anterior cingulate cortex (ACC) co-express c-fos mRNA and CRFR1 after maternal absence. Consistently, excitotoxic ACC lesions inhibited the maternal absence-induced attenuation of Transport Response. These data indicate that the expression of mouse Transport Response is influenced not only by social isolation but also by maternal absence even in their home cage with littermates after PND13, at least partly via CRF-CRFR1 signaling in the ACC.